Impacto sistêmico das periodontites apicais: uma revisão de escopo e relato de caso - Signorelli, Nara Sarmento Macedo (2023)
Introduction: Recently, a new field of study called endodontic medicine has emerged in endodontics, which evaluates the possible systemic impacts of endodontic infections as well as the impacts of systemic diseases, such as end-stage renal disease, on the development and healing of apical periodontitis (AP) of endodontic origin. Within this context, mediators related to oxidative stress have been studied both locally, at the site of the lesion, and systemically, using blood, saliva, and gingival crevicular fluid. The imbalance between oxidant and antioxidant compounds leads to oxidative stress. Oxidative stress has been related to the pathogenesis of AP, and the presence of this pathology has been associated with increased systemic oxidative stress, with a possible impact on other inflammatory disorders. As a result, the number of publications in this area has increased, but the evaluated mediators, types of samples used, and collection and analysis methods have been highly variable. Therefore, this study aimed to 1) map the most commonly used methods for obtaining samples and analyzing reactive oxygen species levels in chronic apical periodontitis; 2) report a case of post-streptococcal glomerulonephritis whose causal factor was an endodontic infection. Methods 1) The methodology used in study 1 followed the PRISMA Extension for Scoping Reviews and was registered in the Open Science Framework ([Blinding]). A systematic search was conducted in the electronic databases MEDLINE (via PubMed), Embase, Scopus, Web of Science, LILACS, SciELO, OATD, and DANS Easy up to January 23, 2023. Eligibility criteria were based on clinical studies, regardless of the design. A bibliometric analysis was also performed to evaluate the occurrence of keywords and journals using VOSViewer software. 2) Study 2 reports the case of an adult patient whose clinical history, laboratory tests, and biopsy report led the attending physician to contact the dentist to investigate a possible oral infection, as the patient presented with necrotic tooth 26 without underlying periodontal disease, caries, or other endodontic treatments. Endodontic treatment of the affected tooth was indicated. Results: 1) The compilation of results from the scoping review shows a total of 18 studies were included. Clinical trials were the most prevalent study design evaluated in this review, followed by observational studies. Among all selected studies, periapical lesions via periapical surgeries or tooth extractions were the most collected samples. Only one study evaluated saliva, and another evaluated gingival crevicular fluid. Twenty-eight different types of oxidative stress analysis were identified, with inducible nitric oxide synthase evaluated by immunohistochemistry being the most prevalent. In the bibliometric analysis, the three most frequent keywords were "apical periodontitis," "oxidative stress," and "inducible nitric oxide synthase." The majority of included studies were published in the International Endodontic Journal. 2) After the conclusion of the clinical case and a 2.5-year follow-up, no disease recurrence or changes in blood and urine tests indicating post-streptococcal glomerulonephritis recurrence were reported. Conclusions: 1) According to the scoping review, we can conclude that although there is a variety of biomarkers to evaluate oxidative stress, it is not possible to identify specific reative nitrogen species or reative oxygen species molecules, as well as antioxidants that can serve as candidate biomarkers to assess the status of AP and potential systemic impacts. Studies involving less invasive methods such as saliva and gingival crevicular fluid are needed. 2) Endodontic infection due to pulp necrosis can be the cause of post-streptococcal glomerulonephritis, and endodontic treatment can aid in the rapid remission of disease symptoms, reducing relapses and restoring the patient's quality of life.